Evaluation of sexual dysfunction in Parkinson's disease between two different regions of Turkey - Kaya, Yasemin; Özer, Feriha; Benli, Erdal; Helvacı Yılmaz, Nesrin; Aydemir, Tuğba; Yancar Demir, Esra (Elsevier Science Bv., 2017)
Objective: In this study, we aimed to evaluate sexual dysfunction (SD) between two different regions of Turkey in patients with Parkinson's Disease (PD). Patients and methods: Forty-three PD patients in Ordu and 71 patients in Istanbul were included. The Unified PD Rating Scale and Hoehn and Yahr Stage (HYS) scale were used to assess disease severity. Cognitive function was assessed by the Mini-Mental State Examination (MMSE). The sexual functions of the patients were evaluated with applying the Turkish version of the Arizona Sexual Experiences Scale (ASEX). Results: Mean age of patients in Istanbul was 67.25 +/- 8.34 years and mean age of patients in Ordu was 67.98 +/- 8.93 (p = 0.66). There was 87.33% SD in Istanbul group and 95.35% in Ordu group (p = 0.20) respectively. In terms of ASEX score, no difference was found between the Istanbul and Ordu groups. ASEX scores were significantly higher in females in both groups. Conclusion: In this study, we have found that living in the different regions of our country does not have an impact on sexual function in PD patients.
WOS: 000412255900021
PubMed ID: 28869860
Keywords: ASEX Score; Parkinson's Disease; Sexual Dysfunction